2011
DOI: 10.5914/tropocean.v39i1.5176
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and interannual variability of the southern south Equatorial Current bifurcation and meridional transport along the eastern brazilian edge.

Abstract: The dynamics of the southern band of the South Equatorial Current (sSEC) near to Brazilian shelf is investigated using recent field observations and a regional numerical modeling approach. The field measurements were obtained from five moorings deployed by German CLIVAR (Climate Variability and Predictability Program) cruises (March 2000-August 2004) along a crossshore line at 11oS. The Regional Ocean Model (ROMS) is used to simulate the circulation and thermohaline structures within the ocean area comprised b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Earlier studies (e.g. Watts and Kontoyiannis, 1990;Johns et al, 2005;Kanzow et al, 2006;Cunningham, 2009) found that subtracting a least-squares exponentiallinear fit of the form P Drift (t) = a 1 − e −bt + ct + d from the pressure time series to be the procedure that works best for the PIES. As the SBE26plus recorders were also equipped with quartz pressure sensors, we decided to "de-drift" all five sensors similarly by subtracting exponential-linear fits as described above.…”
Section: Bottom Pressure Time Seriesmentioning
confidence: 99%
“…Earlier studies (e.g. Watts and Kontoyiannis, 1990;Johns et al, 2005;Kanzow et al, 2006;Cunningham, 2009) found that subtracting a least-squares exponentiallinear fit of the form P Drift (t) = a 1 − e −bt + ct + d from the pressure time series to be the procedure that works best for the PIES. As the SBE26plus recorders were also equipped with quartz pressure sensors, we decided to "de-drift" all five sensors similarly by subtracting exponential-linear fits as described above.…”
Section: Bottom Pressure Time Seriesmentioning
confidence: 99%
“…The BC has been studied by numerous researchers who predominantly attempted to estimate its meridional volume transport based on hydrographic datasets acquired at different latitudes [1,2]. Only a few studies in the scientific literature treat specifically about the interannual variability of the BC volume transport even though many studies describing general dynamic aspects in different variability scales for the whole South Atlantic basin had been published such as Schott et al [3], Stramma et al [4], Lumpkin and Garzoli [5] and Veleda et al [6]. Goni et al [7], using satellite-derived sea height anomaly and sea surface temperature (SST) observations from 1993 to 2008, observed low-frequency variability of the BC front.…”
Section: Introductionmentioning
confidence: 99%